1984
DOI: 10.1002/clc.4960070702
|View full text |Cite
|
Sign up to set email alerts
|

Does alcohol intensify the hemodynamic effects of nitroglycerin?

Abstract: Summary: To evaluate the combined effects of alcohol and nitroglycerin on cardiovascular hemodynamics, Mmode echocardiography and sphygmomanometric blood pressure measurements were perfonned on two groups of nonnal subjects, before and after the administration of nitroglycerin, both in the sober state and during alcohol intoxication. In the first part of the study, 0.5 mg of nitroglycerin was given sublingually to 10 healthy volunteers 5-10 minutes after they had ingested I g/kg body weight of ethanol within a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Alcohol can result in hypotension in individuals taking nitrates. Kupari et al 104 found that, after ethanol ingestion, the immediate beneficial effects of nitroglycerine were still observed, but later, ethanol intoxication did increase susceptibility to hypotension.…”
Section: Interactions Of Alcohol and Drugs Commonly Used In The Elderlymentioning
confidence: 99%
“…Alcohol can result in hypotension in individuals taking nitrates. Kupari et al 104 found that, after ethanol ingestion, the immediate beneficial effects of nitroglycerine were still observed, but later, ethanol intoxication did increase susceptibility to hypotension.…”
Section: Interactions Of Alcohol and Drugs Commonly Used In The Elderlymentioning
confidence: 99%